Nanotube Arrays: In Situ Surface‐Modification‐Induced Superhydrophobic Patterns with Reversible Wettability and Adhesion (Adv. Mater. 12/2013). (18th March 2013) - Lai, Yuekun; Pan, Fei; Xu, Cong; Fuchs, Harald; Chi, Lifeng
<x xml:space="preserve">Abstract</x> A facile, in situ, ink‐regulating approach is developed on page 1682 by Lifeng Chi, Yuekun Lai, and co‐workers for rapidly reversible water wettability and adhesion transition, with a large degree of contrast, on superhydrophobic TiO2 nanotube array film. This finding provides new strategies in the design of siteselective, sticky superhydrophobic patterns for droplet manipulation and cell immobilization. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>